KAJIAN TEKANAN PADA ISOLASI BEBERAPA SENYAWA MINYAK NILAM (Pogostemon cablin Benth) DENGAN METODE DISTILASI FRAKSINASI - Zahrah Eza Arpima; Sarifah Nurjanah; Asri Widyasanti; Bambang Nurhadi; Tita Rialita; Elazmanawati Lembong (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
In the fractional distillation process, the pressure that used is one of the important factors determining the operating conditions to obtain optimal product. This research aims to determine the effect of pressure on the fractinal distillation process of patchouli oil. The research method that used in this research was an experimental method with descriptive analysis. This research was conducted with three treatments that is different pressure treatments and repeated twice. The pressure treatments that used in the fractional distillation process are A = 5 mmHg, B = 10 mmHg, and C = 15 mmHg and arranged to produce five (5) fractions of each treatment. The parameters that measured including the yield of fractional distillation, distillation process time, specific gravity, and refractive index. The lower the pressure used in the distillation process, the greater the yield and the faster the distillation process time. The results of this research indicate that the variation of pressure that used does not have a significant effect on the characteristics of patchouli oil such as specific gravity and refractive index. The application of 5 mmHg pressure is good enough to separate the distillate yield into 5 fractions and is more efficient because it obtains the highest total yield of 93.5% with a distillation process time of 18.16 hours.